Combining combretastatin A4 phosphate with ginsenoside Rd synergistically inhibited hepatocellular carcinoma by reducing HIF-1α via PI3K/AKT/mTOR signalling pathway. (25th December 2020) - Yang, Xinxiu; Gao, Meng; Miao, Mengqi; Jiang, Cuihua; Zhang, Dongjian; Yin, Zhiqi; Ni, Yicheng; Chen, Jing; Zhang, Jian
Abstract: Objectives: Combretastatin A4 phosphate (CA4P), a vascular disrupting agent (VDA), can cause rapid tumour vessel occlusion. Subsequently, extensive necrosis is discovered in the tumour center, which induces widespread hypoxia and the rise of the α subunit of hypoxia-inducible factor-1 (HIF-1α). The aim of this study was to evaluate the inhibition of hepatocellular carcinoma growth by combining CA4P with HIF-1 α inhibitor and investigate the mechanism of this combination. Methods: Ginsenoside Rd (Rd) was used in combination with CA4P to estimate the inhibition effect in HepG2 cells and HepG2 xenograft mouse model. The efficacy of anti-tumour was evaluated by tumour growth curve. The protein expression of HIF-1α and PI3K/AKT/mTOR signalling pathway were analysed by western blot. Key findings: Combination of CA4P and Rd inhibited HepG2 cell proliferation and induced apoptosis in vivo and in vitro . It also increased the necrotic area of the tumour and delayed the tumour growth. Moreover, Rd down-regulated HIF-1α protein expression by inhibiting PI3K/AKT/mTOR signalling pathway. Conclusions: Combination of CA4P and Rd had synergistic anti-tumour effects. The mechanism may be related to the inhibition of HIF-1α by PI3K/AKT/mTOR signalling pathway. This strategy provides a new thought for the combinative therapy of VDAs.